1999
DOI: 10.1046/j.1365-2559.1999.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Sinus histiocytosis with massive lymphadenopathy: evidence for its relationship to macrophages and for a cytokine‐related disorder

Abstract: We conclude that stimulation of monocytes/macrophages via macrophage colony stimulating factor (M-CSF) leading to immune suppressive macrophages represents a main mechanism for the pathogenesis of SHML. The study further provides evidence for the monocyte/macrophage but not dendritic cell differentiation of SHML histiocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
67
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 34 publications
(30 reference statements)
2
67
0
1
Order By: Relevance
“…Interestingly, that study also found mean variant allele frequencies at levels similar to our study, including a KRAS G12D missense variant in RDD. These very recent findings, in addition to our own, challenge the historical notion that RDD is a purely non-clonal, reactive process [1,3,4]. This case is, to the best of our knowledge, the first report of a KRAS K117N missense variant in RDD.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Interestingly, that study also found mean variant allele frequencies at levels similar to our study, including a KRAS G12D missense variant in RDD. These very recent findings, in addition to our own, challenge the historical notion that RDD is a purely non-clonal, reactive process [1,3,4]. This case is, to the best of our knowledge, the first report of a KRAS K117N missense variant in RDD.…”
Section: Discussionsupporting
confidence: 64%
“…Historically, RDD is considered non-clonal and reactive [3,4]. However, RDD lesions have been reported to undergo malignant transformation to histiocytic sarcoma [25,26] and high-grade lymphoma [27] indicating their potential for genomic instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, its expression by macrophages has been documented in various diseases such as Rosai-Dorfman disease (25), multibacillary leprosy (26), and HIV infection (27,28). In all of these conditions, this apparently aberrant expression was demonstrated to be associated with down-or upregulation of other markers, thereby suggesting functional alterations that are probably related to the underlying immune or infectious disorder (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Although the DC origin of MGCs is an attractive supposition, given the lack of specificity of both S-100 protein and fascin, because they are also expressed by macrophages or other cell types (23)(24)(25)(26)(27)(28)38), we think that assessing the DC lineage by merely studying these markers is insufficient to validate such a hypothesis. Whatever their precise ontogeny, the detection of these very characteristic cells in hyperplastic lymphatic tissues of the WR at least has the merit of alerting the pathologist to the possibility of an underlying HIV infection.…”
Section: Discussionmentioning
confidence: 99%